Activities and sources of beta-lactamase in sputum from patients with bronchiectasis. - Dragicevic, P (1989)
beta-Lactamase activity was measured in secretions from patients with bronchiectasis. Of 28 sputum samples, 23 contained measurable amounts of activity; values were significantly higher (P less than 0.01) in purulent samples than in mucoid or mucopurulent samples. beta-Lactamase activity was usually present in saliva collected before and between sputum expectorations, although values for sputum were higher than for either group of saliva samples (P less than 0.025 and P less than 0.005, respectively). This difference suggests that at least part of sputum beta-lactamase activity originates in the bronchial tree. Detailed microbiological study of a further eight specimens (seven were beta-lactamase positive) led to the isolation of Haemophilus influenzae from six, although only two of these isolates were beta-lactamase positive. Several other beta-lactamase-producing organisms were also isolated, including Staphylococcus aureus (n = 3), Escherichia coli (n = 1), Proteus spp. (n = 1), and Bacteroides spp. (n = 3). Size-exclusion high-performance liquid chromatography of the sputum showed several peaks of beta-lactamase activity which usually coeluted in fractions similar to those of their beta-lactamase-positive isolates. Therefore, sources of sputum beta-lactamases are often bacteria not considered truly pathogenic or not isolated during routine bacteriological assessment. These observations should be considered when embarking on antimicrobial therapy in bronchiectatic patients and suggest that increased dosages of penicillins are indicated.